Valorization of Food Processing By-Products - Poiana, Marco; Caponio, Francesco; Piga, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The papers published in this Special Issue report on recent studies investigating the exploitation of by-products produced by the food industry. The topics investigated include the extraction setups used for valuable food waste by-products and their applications as adjuncts to food preparation; the appropriate selection of solvents and extraction processes; and the interactions between extracted fractions and supplementary foods. The papers evaluate a wide variety of foodstuffs and provide results regarding the extension their shelf-lives and activities as functional foods.